Multi-Language Translated Drama Scripts as Reference Information for Actors - Hidayat, Arif; Rafli, Zainal; Iskandar, Ifan (Mitra Palupi, 2024)
Background: Drama texts translated into various languages ​​are a form of communication across linguistic boundaries and a window that reveals the richness of diverse cultures. For actors, engaging in the performance of a multilingual script provides an incredible opportunity to explore the nuanced complexities of different cultures. Actors learn new words and soak up the soul of a culture that may be very different. Purpose: The main aim of this research is to (1) find out the extent to which language variations are used in translated drama scripts and (2) the extent to which language variations influence the way actors understand and portray characters. Design and methods: This research uses a content analysis method on intralingually translated drama texts sourced from the Matara Production archives. Results: The results of this research reveal (1) that three languages ​​are used (English, Indonesian and Sundanese) and (2) that multiple languages ​​are used to show narrative diversity, subtlety of relationships in roles and cultural context. The importance of using regional languages ​​in specific cultural contexts becomes clear, as in the depiction of the local ghost, Kuntilanak, which adds another layer of cultural richness. It can be concluded; this research highlights the significance of the use of multiple languages ​​in the expression and communication of actors. Multilingualism allows actors to convey characters with greater depth, creating an immediate bond with multilingual audiences. Language is not only a means of communication but also a key holder of cultural identity, bringing to life cultural aspects that are difficult to explain in words.